Os desafios da gest??o na educa????o superior privada: um estudo explorat??rio na perspectiva da psicodin??mica do trabalho - Paula, Victor Gomes de (2016)
Higher education has undergone changes in its structural and organizational setup, which has raised concern about his state of expansion and evolution. In the past 20 years, we began a comprehensive reform of public policies aimed to modify the landscape of education in the country, particularly of private higher education. The constant transformation undertaken by governments and society are changing the role of the teacher as well as the functions of universities, leading them to a constant process of adaptation to meet the changing demands and requirements. Thus, private higher education is looking for management models that can support the contemporary changes that focus in teaching and teaching-learning relationship. In this perspective, this research aimed to study the challenges faced by higher education managers in private their work, through an exploratory study based on a theory of work psychodynamics. The research had a qualitative character from the individual listening to managers and teachers from three different institutions of higher education in the Federal District and surrounding areas. Data collection occurred through semi-structured interviews, guided by a roadmap with themes. The interviews followed three axes of analysis, real and prescribed work, individual defense strategies and ethical suffering at work. Regarding the actual and the prescribed stand out unforeseen in the classroom, the demands of the institution, the bureaucracy and the lack of preparation of students coming to higher education and denounce the weakness of basic education. Regarding the individual defense strategies identified the denial of suffering in teaching evidenced by the lack of criticism of the institutional contradictions and denial of work overload. Ethical suffering of managers revealed the extent that these professionals were forced to act against their beliefs and took an institutional discourse at odds with the reality of the work of teachers.